2012
DOI: 10.1007/s00167-012-2176-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of open wedge high tibial osteotomy on the lateral compartment in sheep. Part I: analysis of the lateral meniscus

Abstract: Open wedge HTO does not lead to significant macroscopic and microscopic structural changes in the lateral meniscus after 6 months in vivo. Overcorrection significantly decreases the proliferative activity of the cells in the red-red zone of the middle third in the sheep model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…Osteochondral defects provoked significantly more severe osteoarthritic degeneration of the adjacent cartilage than chondral lesions after 6 months in vivo. This time point was chosen based on the extensive experience with ovine cartilage repair after 6 months by several research groups 15,17,19,20,26,[44][45][46] and the suitability of this observation period to assess the development of osteoarthritis. 5 In accordance, Hepp et al 24 confirmed degenerative perilesional changes already 3 months after creation of cylindrical 7 mm osteochondral defects in ovine femoral condyles.…”
mentioning
confidence: 99%
“…Osteochondral defects provoked significantly more severe osteoarthritic degeneration of the adjacent cartilage than chondral lesions after 6 months in vivo. This time point was chosen based on the extensive experience with ovine cartilage repair after 6 months by several research groups 15,17,19,20,26,[44][45][46] and the suitability of this observation period to assess the development of osteoarthritis. 5 In accordance, Hepp et al 24 confirmed degenerative perilesional changes already 3 months after creation of cylindrical 7 mm osteochondral defects in ovine femoral condyles.…”
mentioning
confidence: 99%
“…Many of these degenerative changes might initiate an inflammatory status and secretion of catabolic factors that lead to development of late-stage osteoarthritis [ 10 ]. In the context of early osteoarthritis, significant correlations between early osteoarthritic changes in the submeniscal tibial plateau cartilage and meniscal degeneration have recently been detected [ 29 ]. Additionally, there appears to be a correlation between meniscal extrusion and cartilage damage in the peripheral region of the tibial plateau, underlining the fact that the submeniscal region is vulnerable to early osteoarthritis [ 30 ], and thus leads to structural and mechanical alterations of the meniscus leading to further implications within the joint [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical result of our case was satisfactory so far, concerns remain about the survival of this procedure. An animal study in sheep has shown that standard correction with a valgus angle of 4.5° has no major detrimental effect on lateral compartment compared to 9° valgus which caused reduced cell numbers and low proliferative activities in the middle third of the vascular zone of lateral meniscus [ 13 ]. From this point of view, we tried to correct the preoperative varus alignment to only slight valgus (2.7°) angle.…”
Section: Discussionmentioning
confidence: 99%